Networking among Russian farmers and their prospects for success. Issue 4 (4th July 2019) - Golovina, Svetlana; Hess, Sebastian; Nilsson, Jerker; Wolz, Axel
ABSTRACT: In most post-socialist economies, private farming has re-emerged after regime change, although even today this sector most often accounts for only a minor proportion of national production. Russian private farmers are reported to dislike formal cooperatives, so this study investigated whether their informal collaborative arrangements may affect their business results. A survey involving personal interviews with 158 randomly chosen private farmers in the Kurgan Region examined whether collaborating farmers are economically more successful and consider their financial situation to be better than that of neighbouring farmers. Ordinary least square and ordered probit regression analysis indicated that farmers with stronger networks are more successful in terms of farm wealth, and also relative to the financial situation of their immediate neighbours. This suggests that success among private farmers in a post-socialist setting is related to their networks.